CO2 storage capacity of coal seams: a screening and geological review of carboniferous coal formations of Kazakhstan - Mohammad Asif; Medet Junussov; Sotirios Nik. Longinos; Randy Hazlett; Sandugash Satibekova (Springer Science and Business Media LLC, 2025)
The increasing atmospheric CO 2 concentration linked to human activity results in global warming by the greenhouse effect. This anthropogenic CO 2 may be sequestrated into geological formations, e.g., porous basalts, saline aquifers, depleted oil or gas reservoirs, and unmineable coal seams. Furthermore, carbon capture, utilization, and storage (CCUS) methods are an acceptable and sustainable technology to meet the goals of the Paris Agreement, in which Kazakhstan is expected to reduce greenhouse gas emissions by 25% compared with the 1990 level. Unmineable coal seams are an attractive option among all geostorage solutions, as CO 2 sequestration in coal comes with an income stream via enhanced coalbed methane (ECBM) recovery. This paper identifies four carboniferous coal formations, namely Karagandy, Teniz-Korzhinkol, Ekibustuz, and Chu coal basins of Kazakhstan, as CO 2 geostorage solutions for their unmineable coal seams. The ideal depth of CO 2 storage is identified as 800 m to ensure the supercritical state of CO 2 . However, the Ekibustuz coal basin fails to meet the required depth of 800 m in its unmineable coal seams. The conventional formula for calculating CO 2 storage in coal basins has been modified, and a new formula has been proposed for assessing the CO 2 storage potential in a coal seam. The CO 2 storage capacities of unmineable coal seam of these coal basins are 24.60 Bt, 0.61 Bt, 14.02 Bt, and 5.42 Bt, respectively. The Langmuir volume of the coal fields was calculated using the proximate analysis of coalfields and found to vary between 36.42 and 98.90 m 3 /ton. This paper is the first to outline CO 2 storage potential in Kazakhstani coal basins, albeit with limited data, along with a detailed geological and paleographic review of the carboniferous coalfields of Kazakhstan. A short overview of the CO 2 -ECBM process was also included in the paper. Instead of any experimental work for CO 2 storage, this paper attempts to present the CO 2 storage capacity of carboniferous coal formation using the modified version of previously determined formulas for CO 2 storage.
Keywords: Coal; Coal mining; Carboniferous; Mining engineering; Geology; Enhanced coal bed methane recovery; Greenhouse gas; Petroleum engineering; Coalbed methane; Environmental science; Geochemistry; Structural basin; Waste management; Engineering; Geomorphology; Oceanography; type of access: open access